pem, me, peng, budi Pengelolaan Sampah Rumah Tangga yang Inovatif Berbasis Partisipasi Aktif Masyarakat di Nagari Situjuah Banda Dalam - Mislaini Rahman; Nurwanita Ekasari Putri; Ely Vebriyanti (Agriculture Faculty, Universitas Lampung, 2026)
Situjuah Banda Dalam Village is a village in Situjuah Limo Nagari District, 50 Kota Regency. It has a relatively high population density and community activities predominantly focused on agriculture, trade, and micro, small, and medium enterprises (MSMEs). These activities result in increasing household and business waste, but it has not yet been fully managed in an integrated manner. The current waste management system remains conventional and suboptimal. Most waste is managed independently by communities by burning, burying, or dumping it in open areas, including rivers, which contributes to environmental pollution. An effective Integrated Waste Processing Facility is not yet available.The objectives of this Community Service Program include: increasing public awareness and participation, reducing household and business waste generation, establishing a village-based waste management system, developing a waste-based circular economy, preserving the environment, and improving public health.The program's outcome is